Knowledge, Attitude and Practices of Breast Self-Examination Amongst Indian Women: A Pan-India Study - Sachdeva, Shubhangini; Mangalesh, Sridhar; Dudani, Sharmila (Asian Pacific Journal of Cancer Care, 2021)
Objective: Breast Cancer is the leading cause of mortality and morbidity amongst Indian females. Breast self-examination (BSE) as an early detection modularity can have a profound effect on lowering mortality, if it is practiced regularly. The aim of this study was to assess the knowledge, attitude, and practice of Breast Self-examination amongst Indian women, aged 30 years and above. Methods: A validated questionnaire, consisting 35 questions measuring ‘Knowledge, Attitudes and Practice of Breast Self-Examination’ was widely circulated amongst 1000 females throughout India and responses were collected for a duration of 3 weeks, from 2nd, September 2020 to 23rd,September 2020. Results: Despite having knowledge about the technique of performing BSE, the respondents did not have a positive attitude towards it and were reluctant to practice BSE. A total of 54.4%, 15.1%, 21.3% and 9.2% of respondents were from the Northern, Southern, Western and Eastern regions of India, respectively. The overall median (IQR) KAP score was 70.0 (16.0) out of a maximum of 110. The knowledge, attitude and practice domain scores were 22.0 (5.0), 36.0 (7.0), and 13.0 (8.0) out of a maximum of 30, 52 and, 28, respectively. All three individual score domains were significantly correlated with each other and the total score. Conclusion: Despite having knowledge about the technique of performing BSE, the respondents did not have a positive attitude towards it and were reluctant to practice BSE.